2015
DOI: 10.1038/ncomms7769
|View full text |Cite
|
Sign up to set email alerts
|

CDK1 structures reveal conserved and unique features of the essential cell cycle CDK

Abstract: CDK1 is the only essential cell cycle CDK in human cells and is required for successful completion of M-phase. It is the founding member of the CDK family and is conserved across all eukaryotes. Here we report the crystal structures of complexes of CDK1–Cks1 and CDK1–cyclin B–Cks2. These structures confirm the conserved nature of the inactive monomeric CDK fold and its ability to be remodeled by cyclin binding. Relative to CDK2–cyclin A, CDK1–cyclin B is less thermally stable, has a smaller interfacial surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
185
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(200 citation statements)
references
References 69 publications
7
185
3
2
Order By: Relevance
“…4A, Right). These highly coevolving interfaces suggest that CDK1 may interact with two CKS1 at the two different binding sites (residues are shown in SI Appendix, Table S1), which is consistent with a previous structural study (39). Remarkably, the interface interaction score for site 2 of CDK1 to site 1 of CKS1 is much stronger than the one for site 1 of CDK1 to site 2 of CKS1.…”
Section: Identifying the Druggable Interface For Mdm2 Homodimer And Tsupporting
confidence: 77%
See 1 more Smart Citation
“…4A, Right). These highly coevolving interfaces suggest that CDK1 may interact with two CKS1 at the two different binding sites (residues are shown in SI Appendix, Table S1), which is consistent with a previous structural study (39). Remarkably, the interface interaction score for site 2 of CDK1 to site 1 of CKS1 is much stronger than the one for site 1 of CDK1 to site 2 of CKS1.…”
Section: Identifying the Druggable Interface For Mdm2 Homodimer And Tsupporting
confidence: 77%
“…Recently, the CDK1-CKS1 complex was crystallized with four CDK1-CKS1 heterodimers in the asymmetric unit (39). This structure revealed that the C lobe of the CDK1 interacts with two CKS1 proteins at their N lobe.…”
Section: Identifying the Druggable Interface For Mdm2 Homodimer And Tmentioning
confidence: 99%
“…In mammalian, cell cycle is controlled by a subfamily of cyclin-dependent kinases (CDKs), dysregulation of which induce unscheduled proliferation [45]. CDK1 is a member of the CDK family, besides, it is the only essential cell cycle CDK in human cells [46]. As a result, CDK1 might involve in the development of ATC through the pathway of cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1 is the founding member of the CDK family (33), and it is the only CDK to partner cyclin B, which starts to accumulate in S phase (34). CDK1-cyclin B1 complexes are also thought to regulate several events during G 2 /M transition (10,35). Silence of cyclin B1 inhibits proliferation by arresting cells in G 2 /M phase (36).…”
Section: Discussionmentioning
confidence: 99%